Teachers’ attitudes and students’ language preferences on code-switching in English classrooms: A mixed-method study at Instituto São João de Brito, Timor-Leste - Pires, Sidonio Antonio (Abdul Media Literasi, 2025)
This study investigates the role of code-switching in English language teaching at Instituto São João de Brito, Timor-Leste, a multilingual setting where English is taught as a foreign language. Building on existing research highlighting the importance of code-switching in facilitating teaching and learning, this study explores teachers’ attitudes and students’ language preferences in classes where code-switching is employed. A mixed-method approach was adopted, involving four teachers and fifty students who participated in questionnaires and semi-structured interviews. The findings reveal that teachers recognise the value of code-switching in enhancing student understanding, participation, and teaching methods. Quantitative results show that 60% of students are flexible with code-switching, while 90% prefer increased use of English in class. The study’s findings contribute to understanding how code-switching can effectively be utilised in English language teaching practices in multilingual settings, highlighting the need for a balanced approach that promotes linguistic flexibility and English language proficiency. The implications of this study can inform teaching practices and policies in similar multilingual contexts, ultimately enhancing the effectiveness of English language instruction.